INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA KEGIATAN EKSTRAKURIKULER SYIAR KEGIATAN ISLAM (SKI) DALAM MENUMBUHKAN KARAKTER ISLAMI - Naomi Fahma (MAMBA'UL 'ULUM, 2023)
This research aims to explain the process of internalizing the values of Islamic religious education through SKI extracurriculars at senior high school to find out the internalized values of Islamic religious education, and to find out the implications of internalizing the values of Islamic religious education through extracurriculars to foster Islamic character in senior high school. This type of research uses descriptive qualitative research methods. Data collection used was observation, interviews and documentation. The results of the research show that the process of internalizing the value of Islamic religious education through the SKI extracurricular at senior high school in cultivating Islamic character has been going quite well. There are four stages carried out in internalizing the values of Islamic religious education at senior high school, namely the value transformation stage, value transaction, value transinternalization, and correction or evaluation. The values that are internalized are the values of i'tiqadiyyah, khuluqiyyah, and amaliyyah. These values are internalized through religious activities at school such as tadarus Qur'an, congregational noon prayers, kultum and tahfidz Qur'an, Friday imtaq, Friday infaq, hadroh, halaqoh, commemoration of Islamic holidays, and Islamic boarding schools.